Дистанційна освіта у медичному університеті в умовах військового стану - Звягіна, Ганна Олександрівна; Потоцька, Олена Іванівна (Запорізький державний медико-фармацевтичний університет, 2024)
Статтю присвячено викладанню дисциплін у ВНЗ в дистанційному форматі. Увагу приділено з’ясуванню поняття «дистанційна освіта» та її основним режимам: синхронному і асинхронному, їх перевагам і недолікам. Виділено тьюторинг як особливу форму академічної підтримки та його місце в навчальному процесі. На прикладі Запорізького державного медико-фармацевтичного університету відображено роботу медичного ВНЗ в умовах воєнного стану. Розглянуто змішану форму навчання як більш зручну для викладання дисциплін практичного спрямування у медичному університеті. The article is devoted to the teaching disciplines at the university in a distance format. Attention is paid to clarifying the concept of "distance education". The modes of distance education are considered. The main advantages and disadvantages of synchronous and asynchronous modes are determined. Tutoring is highlighted as a special form of academic support. Its role in the educational process is determined. The main attention is paid to the work of the medical university during the martial law in Ukraine. The work of Zaporizhzhya State Medical and Pharmaceutical University was chosen as an example. An alternative form of distance learning is proposed ˗ blended learning. It is defined as more convenient for teaching practical disciplines.
Keywords: дистанційне навчання; змішана форма; синхронний та асинхронний режими; тьюторинг; blended learning; distance learning; synchronous and asynchronous modes; tutoring